2007
DOI: 10.1590/s1519-69842007000300014
|View full text |Cite
|
Sign up to set email alerts
|

Total-Hg and organic-Hg in Cephalopholis fulva (Linnaeus, 1758) from inshore and offshore waters of NE Brazil

Abstract: To investigate whether source proximity or bioavailability is the major factor controlling both Hg concentration and Hg speciation in marine fishes, total-and organic-Hg content in muscle and liver tissues from different populations of Cephalopholis fulva (piraúna) from inshore and offshore waters of the Brazilian northeastern coast were analyzed. Average total-Hg in muscle (104 ng.g -1 w.w.) and liver (2,865 ng.g -1 w.w.) tissues, as well as organic-Hg concentrations in muscle (169 ng.g -1 w.w.) and liver (1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
0
3
0
5
Order By: Relevance
“…At HQ < 1.0 exposure level is smaller than the reference dose; meaning that daily exposure to this level is unlikely to cause adverse effects to consumers. (Lacerda et al, 2007). maximum of 680 ng.g -1 .…”
Section: Hq=e/rfdmentioning
confidence: 98%
See 1 more Smart Citation
“…At HQ < 1.0 exposure level is smaller than the reference dose; meaning that daily exposure to this level is unlikely to cause adverse effects to consumers. (Lacerda et al, 2007). maximum of 680 ng.g -1 .…”
Section: Hq=e/rfdmentioning
confidence: 98%
“…Recent studies in this region reported overall low Hg concentrations in fish, but also high Hg concentrations in fish species occupying higher trophic levels like Rhinobatos percellens, Cephalopholis fulva and Scomberomorus cavalla (Costa & Lacerda, 2009;Lacerda et al, 2007 and2013). Some of these species are also the most appreciated by consumers, but because the greater economic value, they constitute a smaller part of the local fish meals, therefore resulting in a lower exposure risk to Hg due to fish consumption by artisanal fishery communities (Costa & Lacerda, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…7 Além disto, a construção de barragens reduz ainda mais o aporte fluvial para o mar. [8][9][10] Entretanto, de forma similar ao que ocorre no Ártico, concentrações elevadas de Hg, por exemplo, também vem sendo medidas na biota marinha local, 11,12 sugerindo aumentos da contribuição continental do metal apesar de ocorrer a diminuição progressiva do aporte fluvial total. Neste trabalho, este paradoxo é discutido com base em dados plurianuais dos fluxos de Hg e da hidrodinâmica do rio Jaguaribe (CE), o principal rio do semiárido do nordeste brasileiro.…”
Section: Introductionunclassified
“…Apesar do conhecimento sobre diversos elementos metais em peixes mostrar que a musculatura é o tecido em que pode ocorrer os menores valores de concentração (Lacerda et al, 2007;Pierron et al, 2008;), a musculatura foi escolhida, pois é amplamente consumida não somente pelos predadores, é de mais fácil conservação e há dados disponíveis na literatura para comparações.…”
Section: Nesse Cenário a 5th International Conference On Marine Pollunclassified
“…A fase do ciclo de vida é importante para determinar os níveis de mercúrio no tecido dos peixes. As concentrações geralmente aumentam com o ganho de peso, tamanho e com a idade de actinopterígios e elasobrânquios, mas nem sempre esse padrão ocorre (Marins et al, 1998;Lacerda, 2000;Lacerda et al, 2007;Costa & Lacerda, 2009). Porém, maiores concentrações em musculatura de peixes foi encontrada em espécies onívoras, enquanto as mais baixas em detritívoros (Alonso et al, 2000) Levantamentos sobre a presença de mercúrio no sedimento do sistema (Sorensen, 1991;Lemly, 1998), entretanto, a acumulação no músculo parece ser a única que sofre influência direta do hábito alimentar (Seixas et al, 2006).…”
Section: Manganês (Mn)unclassified